Moving the needle towards health equity: A policy-driven transdisciplinary approach to address health disparities for vulnerable communities. (December 2018) - Reddy, Swapna; Paode, Pooja; Speer, Matthew; Semenchuk, Nicholas; Goble, Kyle; White, Adrienne
Objectives: Policymakers, health services researchers, community leaders and health care delivery organisations are key stakeholders in addressing economic, environmental, social and systemic barriers to health equity in vulnerable communities. However, they often operate in silos, leaving gaps in efforts to effectively address health disparities. It is important to develop a new approach to influencing responsive health equity–focused policies. Design: An innovative, collaborative model is outlined that leverages strengths across these four stakeholders to reduce inequity in target populations. The model brings together undergraduate and graduate student researchers in a front-end policy partnership with elected officials based on mutually agreed-upon commitment to address local health disparities impacting the policymaker's constituency. Setting: Students and faculty at Arizona State University partnered with the office of a Phoenix City Council member representing a constituency largely comprised of low-income and Hispanic community members. Method: Relationships were developed with the policymaker specifically targeting food insecurity and paediatric asthma. Graduate student researchers conducted academic placements within the elected official's office, attended relevant municipal meetings, engaged with local community-based organisations and partnered with a major academic medical centre to collect data and understand current efforts related to the two focus areas. Results: Elected officials were provided with a policymaker-tailored toolkit including a current state analysis, stakeholder assessment and recommendations for action. Collective discussion took place concerning the strengths and limitations of stakeholders' ability to improve population health and present findings from the model's first application to local government. Conclusion: By ensuring 'buy-in' from policymakers at the onset of collaboration, stakeholders worked as a transdisciplinary team to translate academic research into actionable policy to benefit high-need communities. This model adopted can potentially accelerate and improve the development and implementation of actionable policies, thereby increasing social capital and building relationships with policymakers to address the root causes of health inequities.